Perspektif Hukum Islam dalam Penggunaan Sisa Uang Nasabah di Pegadaian Syariah - Nurbaiti Nurbaiti; Bahrul Ma'ani; Ahmad Faruk; Fathurrahman Fahturrahman (INNOVATIO: Journal for Religious Innovation Studies, 2016)
This study aims to reveal the distribution of the remaining customer money by Pawnshop and a review of Islamic law against the remaining money of the customer. Using a qualitative approach with data collection methods through observation, interviews, and documentation, the research obtained results and conclusions: first, the calculation of residual money made by the Pegadaian was very beneficial for both parties. Second, the remaining money from the auction of goods pawned after being used to cover loans, capital and interest, and auction fees, will be returned to the relevant customer. The period of validity of the remaining money from the auction for one year at pawnshop, if the customer when confirmed by the Pawnshop as if it does not care but disappears, the remaining money will be kept by the pawnshop for one year and during that time the Pawnshop continues to confirm money once a month the rest. If it has exceeded the limit of one year, the remaining money becomes the property of pawnshop. Third, the settlement when the pawner cannot return the money at maturity and the return of the remaining money from the sale of pawning goods is in accordance with the Islamic Shari'a, because in its implementation there are elements of helping fellow Muslims and providing concessions, conveniences, and trust, highly recommended by Islamic law.